Teknik Perancangan Undang-Undang yang Responsif terhadap Perubahan Sosial - Maulia Nurfadillah (JURNAL ILMIAH NUSANTARA, 2025)
Responsive legislative drafting techniques for social change are essential to ensure that legislative products reflect the dynamic needs and aspirations of society. In this context, public participation becomes a key element, where active community involvement in every stage of legislative drafting can avoid dissatisfaction and rejection of the resulting regulations. This article discusses a responsive legislative drafting model, which includes the stages of planning, public consultation, and evaluation. With a multidisciplinary approach and bottom-up principles, the legislative process can be more adaptive to social change. This study also highlights the challenges faced in implementing this technique and the need for awareness from lawmakers to respond substantially to public aspirations. Through the application of responsive drafting techniques, it is hoped that the resulting laws can provide legal certainty, justice, and welfare for all levels of society